Implementasi Model Problem Based Learning Secara Daring Pada Pembelajaran Matematika Untuk Meningkatkan Hasil Belajar Siswa - Raudatul Jenah; Nurul Wahdah; Nur Inayah Syar (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
This study was prompted by students' difficulty in mathematics, particularly on the material to the power of three and the cube root. The use of learning methods in schools is still teacher-centered, therefore students are not overly engaged in the learning process. Online learning is the strategy employed by teachers in the classroom nowadays. The purposes of this study were to determine implementation of online Problem Based Learning Models in mathematics learning, the improvement of student learning outcomes after the application of online the Models in mathematics learning, and how much improvement of student learning. The research method employed was a quantitative approach combining experimental research and a pre-experimental design. The findings revealed that the online problem-based learning model has been implemented on the cube of the third material and the cube root on the teacher and student observation sheets in all phases and produced very good results, and a sig value of 0.00 indicates a substantial increase in the results of mathematics learning outcomes for class V on pretest and posttest data. Based on the findings of the N-Gain score test calculation, it was discovered that the average value of the N-Gain score using the online problem-based learning model was 0.6985, putting it in the moderate category for improving student learning outcomes.